PENGARUH KINERJA KEUANGAN DAN FAKTOR EKONOMI MAKRO TERHADAP RETURN SAHAM PERUSAHAAN REAL ESTATER DAN PROPERTY TAHUN 2001 – 2004 - Suhaeli, Dahli Suhaeli; Tri, Sartono Tri (Jurnal Analisis Bisnis Ekonomi, 2005)
Return saham represent one of factors to motivate investor and represent reward of invesment which share done. Return can assess from level of basal factor company specified period. As for intention of this research that is to know what is basal factor macro factor and company economics have influence really, to share return. In this research the are 16 company taken as sample that is from year 2001 until 2004. Macro and Basal factors economics in this research Current Ratio, Return On Equity, On Asset Return, Net Profit Margin, Ratio Earning Price, Earning per value book price share, inflation, rupiah rate American Dollar, Indonesia bank rate that is as independent variaable while as variable of dependen share return. Result of research indicate tha at a time independent wariable in this research have influence really and very signifikan to share return. As for variation of return share capable to be explained by independent variables equal to 67,7% and the rest equal to 32,3% expalined by other variable which not covered in this research. While by parcial, variable of Return On Equity, On Asset Return, Net Profit Margin, ratio earning price, earning per share, value book price, rupiah rate to American Dollar, Indonesia bank rate have influence of signifikan to share return while variable which not have ann effect on to share return varible of curren inflatin and ratio.